Competitive consequences determined by phenotypic but not genetic distance: A study with asexual water flea genotypes. (21st June 2022) - Tian, Xiaofei; Ohtsuki, Hajime; Urabe, Jotaro
Abstract: How evolutionary relatedness influences the strength of competitive interactions among genetically isolated populations has been a long‐standing interest in ecology. Darwin's 'Competition‐Relatedness Hypothesis (CRH)' states that, since closely related species should compete more strongly, they are less likely to coexist, while Herbert's 'Bimodal Competition Hypothesis (BCH)' predicts that competitive exclusion is less likely to occur when the competing species are genetically close or distant. To test these hypotheses, we experimentally examined the difference in the competitive ability and life tables of fecundity and survivorship among four different genotypes of asexual Daphnia cf. pulex that diverged from a single ancestral genotype. The experiments showed that the competitive consequences differed depending on the pairing of the competing genotypes, and that the degree of the competitive exclusion was lower when the competing genotypes were genetically closer to each other. These results partially supported the BCH but not the CRH at all. More importantly, the degree of competitive exclusion was better predicted by the phenotypic rather than genetic distances between the competing genotypes. The life table experiments revealed that competitively inferior genotypes had higher early reproduction rates, but survival rates decreased with age and thus body size, probably a result of selection by predation pressures found in nature. These results indicate that competitive superiority is highly dependent on selection pressures that given organisms have been evolutionally subjected to, and, that genetic similarity is not necessarily an appropriate measure for predicting the completive exclusion on an ecological time‐scale. To predict competitive relationships among the organisms, it is essential to comprehend their phenotypic differences rather than simply knowing their genetic or phylogenetic relationships. Read the free Plain Language Summary for this article on the Journal blog. Abstract : A free Plain Language Summary can be found within the Supporting Information of this article. 要 旨: 種間競争の強さに近縁性がどのように影響するかは、生態学における長年の関心事である。Darwinの「近縁者競争仮説」は、近縁種ほど、生活要求環境が似ているはずなので、共存しにくくなるとし、Hebertの「二峰性競争仮説」では、競争する種が遺伝的に近い場合と遠い場合で競争排除が起こりにくくなると予測している。 これらの仮説を検証するために、単一の祖先遺伝子型から分岐した絶対単為生殖型のミジンコ 4遺伝子型の間で競争実験を行い、競争の排除の程度と繁殖力・生存率などとの関係を実験的に調べた。 実験の結果、競合する遺伝子型のペアリングによって競争の結果が異なること、競合する遺伝子型が遺伝的に近いほど競合排除の度合いが低くなること示された。この結果は、「二峰性競争仮説」を部分的に支持するが、「近縁者競争仮説」は全く支持しない。さらに重要なことは、競合する遺伝子型間の遺伝的距離よりも、表現型の類似性のほうが競争排除の程度をより良く説明することが分かった。 繁殖と生残の生命表から、競争的に劣る遺伝子型は初期の繁殖率は高いが生存率が年齢とともに低下することが明らかになったが、これはおそらく捕食圧の高い環境で有利になるためであろう。 これらの結果は、競争優位性は、個々の遺伝子型（あるいは種）が進化的に受けてきた選択圧に大きく依存すること、また、遺伝的類似性は生態学的時間スケールでの競争排除を予測する尺度として適切ではないことを示している。生物間の競争関係を予測するためには、単に遺伝的・系統的な関係を知るだけでなく、表現型の違いを理解することが不可欠である。